Screening analysis of viral hepatitis A, B and C infection from 2013 to 2020 in Wasit Province, Iraqi - Hameed, Mustafa Abdul Kareem; Sagban, Sahbaa Hafedh; Mahdi, Hayder Talib (Journal of Kerbala for Agricultural Sciences, 2022)
A total of 1553 individuals who were diagnosed with hepatitis A, B, and C virus infections at Waist Health Centers between 2013 and 2020 were investigated. After using statistical program, the results show the viral hepatitis n male more than female also the disruption of type B viral hepatitis more when comparted with other types.